1981
DOI: 10.1042/bj1980211
|View full text |Cite
|
Sign up to set email alerts
|

The hypothalamic–hypophyseal–gonadal regulation of hepatic glutathione S-transferases in the rat

Abstract: Hepatic glutathione S-transferase activities were determined with the substrates 1,2-dichloro-4-nitrobenzene and 1-chloro-2,4-dinitrobenzene. Sexual differentiation of glutathione S-transferase activities is not evident during the prepubertal period, but glutathione conjugation with 1,2-dichloro-4-nitrobenzene is 2-3-fold greater in adult males than in females. Glutathione conjugation with 1-chloro-2,4-dinitrobenzene is slightly higher in adult males than adult females. No change in activity was observed after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…It has, however, been reported that the activities of GSTs vary during development in the rat and mouse [12,13] and that these enzymes are regulated by sex hormones [13,14]. A sexual di-morphism in the isoenzyme pattern of cytosolic GSTs [15] and in activities towards several substrates such as CDNB and 1,2dichloro-4-nitrobenzene (DCNB) [16] has been observed in rat liver. A regulatory mechanism involving the pituitary has also been demonstrated both in the liver and the adrenal by ourselves [17] and by others [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has, however, been reported that the activities of GSTs vary during development in the rat and mouse [12,13] and that these enzymes are regulated by sex hormones [13,14]. A sexual di-morphism in the isoenzyme pattern of cytosolic GSTs [15] and in activities towards several substrates such as CDNB and 1,2dichloro-4-nitrobenzene (DCNB) [16] has been observed in rat liver. A regulatory mechanism involving the pituitary has also been demonstrated both in the liver and the adrenal by ourselves [17] and by others [16].…”
Section: Introductionmentioning
confidence: 99%
“…A sexual di-morphism in the isoenzyme pattern of cytosolic GSTs [15] and in activities towards several substrates such as CDNB and 1,2dichloro-4-nitrobenzene (DCNB) [16] has been observed in rat liver. A regulatory mechanism involving the pituitary has also been demonstrated both in the liver and the adrenal by ourselves [17] and by others [16]. We found increased levels of several GSTs in both these organs after hypophysectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Although these proteins can be induced by xenobiotics such as 3-methylcholanthrene, phenobarbital and trans-stilbene oxide in the liver, such induction does not seem to occur in the adrenal [7,5]. Hormonal regulation of glutathione transferases in several organs, including the adrenal, is, however, known to occur [18][19][20]. In a previous study we have shown increased levels of several of these isoenzymes in the rat adrenal in response to hypophysectomy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, DES females as well as the other treatment groups respond adequately to cytochrome P-450 and P-448 inducers to be equally capable of metabolizing and disposing of the procarcinogen, AFB1. Hence, altered imprinting of metabolism such as evidenced by altered endocrine secretions (25,34), enzyme levels (25-27/34), and carcinogen-DNA adduct levels can be modulated by activational mechanisms (27,41).…”
Section: Discussionmentioning
confidence: 99%